2020
DOI: 10.1590/1413-81232020257.21482018
|View full text |Cite
|
Sign up to set email alerts
|

Desnutrição e fatores associados em crianças quilombolas menores de 60 meses em dois municípios do estado do Maranhão, Brasil

Abstract: Resumo O objetivo deste artigo é avaliar a prevalência de desnutrição em crianças menores de 60 meses residentes em comunidades remanescentes de quilombos de dois municípios do estado do Maranhão e seus fatores associados. Estudo transversal com amostra de 372 crianças realizado em agosto de 2015. Foram coletadas informações socioeconômicas, demográficas, maternas e das crianças. A antropometria seguiu o proposto pela Organização Mundial da Saúde. Foram calculados os índices estatura para idade e peso para est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 16 publications
(39 reference statements)
2
9
0
17
Order By: Relevance
“…Research [ 35 ] has indicated that child malnutrition could have ceased to be a public health problem over the last decade in Brazil through the maintenance of economic and social policies that allow access to essential services and increase the incomes of the poorest people. However, this situation did not materialize; thinness and accentuated thinness, although reduced, have persisted as a public health problem in more vulnerable regions [ 36 ]. Additionally, the “dynamics of the double burden of malnutrition” [ 4 ] show that stunting, weight loss and thinness have decreased, whereas excess weight has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Research [ 35 ] has indicated that child malnutrition could have ceased to be a public health problem over the last decade in Brazil through the maintenance of economic and social policies that allow access to essential services and increase the incomes of the poorest people. However, this situation did not materialize; thinness and accentuated thinness, although reduced, have persisted as a public health problem in more vulnerable regions [ 36 ]. Additionally, the “dynamics of the double burden of malnutrition” [ 4 ] show that stunting, weight loss and thinness have decreased, whereas excess weight has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Para o autor, as condições de vida enfrentadas pelas famílias rurais estão relacionadas a outros fatores, como menor renda per capita e baixa escolaridade, que, somadas, podem ser consideradas elementos determinantes na situação alimentar. Nesse sentido, Silveira e colaboradores [34] , em estudo com crianças no Maranhão, encontraram percentuais de A/I (15,1%) e P/I (7%) abaixo dos achados paraenses e já constatavam que moradores de comunidades tradicionais, como os quilombolas, convivem com limitadores na melhora do estado nutricional, como baixa renda e escolaridade, informalidade nos vínculos empregatícios e acesso dificultado a bens e serviços, fatores observados no banco de dados do Mapa InSAN2018 que apresentaram forte significância estatística. Dessa forma, em uma mesma área rural, cabe verificar quais os fatores de impacto que incidem nos grupos, tornando as vulnerabilidades tão acentuadas.…”
Section: Quão Grave é a Desnutrição Infantil Quilombola Na Amazônia P...unclassified
“…Short stature and overweight are two nutritional problems that stand out for their negative effects on children's health. These conditions may impair school performance, reduce social capital in the future [1][2][3] , make children more susceptible to repetitive infectious processes [4][5][6] , increase the chance of infant mortality 7,8 , in addition to predisposing to chronic non-communicable diseases in the future 9,10 . In a more unfavorable socioeconomic context, children are more vulnerable to the double burden of nutritional problems.…”
Section: Introductionmentioning
confidence: 99%